Deficient transcription of XIST from tiny ring X chromosomes in females with severe phenotypes. - Migeon, B R (1993)
The severe phenotype of human females whose karyotype includes tiny ring X chromosomes has been attributed to the inability of the small ring X chromosome to inactivate. The XIST locus is expressed only from the inactive X chromosome, resides at the putative X inactivation center, and is considered a prime player in the initiation of mammalian X dosage compensation. Using PCR, Southern blot analysis, and in situ hybridization, we have looked for the presence of the XIST locus in tiny ring X chromosomes from eight females who have multiple congenital malformations and severe mental retardation. Our studies reveal heterogeneity within this group; some rings lack the XIST locus, while others have sequences homologous to probes for XIST. However, in the latter, the locus is either not expressed or negligibly expressed, based on reverse transcription-PCR analysis. Therefore, what these tiny ring chromosomes have in common is a level of XIST transcription comparable to an active X. As XIST transcription is an indicator of X chromosome inactivity, the absence of XIST transcription strongly suggests that tiny ring X chromosomes in females with severe phenotypes are mutants in the X chromosome inactivation pathway and that the inability of these rings to inactivate is responsible for the severe phenotypes.